Polypharmacy and the occurrence of potential drug interactions in geriatric Covid-19 patients in Karawang General Regional Hospital, Indonesia - Khairani, Sondang; Manninda, Reise; Sarah, Mutia (Faculty of Pharmacy, Universitas Pancasila, 2024)
The management of COVID-19 treatment continues to evolve by involving various types of drugs both symptomatic and supportive therapy. COVID-19 infection with comorbid conditions in geriatric patients can have an effect on increasing drug use and the potential for drug interactions. The purpose of the study was to determine whether there is a relationship between the level of polypharmacy and the incidence of potential drug interactions at Karawang Regency Hospital for the period January to December 2021. The research method used was a cross-sectional study design. The data collected was hospital secondary data with retrospective data type and statistical analysis using Spearman Rho. The research material used was medical record data from 182 samples using the total sampling method. Based on the results of the study, it was found that as many as 108 (59.3%) patients received treatment with a total of 5-9 types of drugs. Potential drug interactions were experienced by 148 (81.3%) patients with a total of 764 events. There is a relationship between the level of polypharmacy and the potential incidence of drug interactions (r: 0.537, p: <0.001).